Suppression of integrin α3β1 in breast cancer cells reduces COX-2 gene expression and inhibits tumorigenesis, invasion, and crosstalk to endothelial cells - Mitchell, Kara (2010)
Integrin receptors for cell adhesion to extracellular matrix have important roles in promoting tumor growth and progression. Integrin α3β1 is highly expressed in breast cancer cells where it is thought to promote invasion and metastasis; however, its roles in regulating malignant tumor cell behavior remain unclear. In the current study, we used short-hairpin RNA (shRNA) to show that suppression of α3β1 in a human breast cancer cell line, MDA-MB-231, leads to decreased tumorigenicity, reduced invasiveness, and decreased production of factors that stimulate endothelial cell migration. Real-time PCR revealed that suppression of α3β1 caused a dramatic reduction in expression of the cyclooxygenase-2 (COX-2) gene, which is frequently over-expressed in breast cancers and has been exploited as a therapeutic target. Decreased COX-2 was accompanied by reduced prostaglandin E2 (PGE(2)), a major prostanoid produced downstream of COX-2 and an important effector of COX-2 signaling. shRNA-mediated suppression of COX-2 showed that it has a role in tumor cell invasion and crosstalk to endothelial cells. Furthermore, treatment with PGE(2) restored these functions in α3β1-deficient MDA-MB-231 cells. These findings identify a role for α3β1 in regulating two properties of tumor cells that facilitate cancer progression: invasiveness and ability to stimulate endothelial cells. They also reveal a novel role for COX-2 as a downstream effector of α3β1 in tumor cells, thereby identifying α3β1 as a potential therapeutic target to inhibit breast cancer.